Evaluation of Cervical Cancer Screening System using Visual Inspection with Acetic Acid (VIA) Method in Bantul District 2023 - Rohmah, Nilna Saadatar; Firdaus, Muhammad Reza; Aryanto, Samsu; Wiratama, Bayu Satria (Universitas Teuku Umar, 2025)
Background: Cervical cancer remains a significant public health challenge globally, particularly in Indonesia, where it disproportionately affects women of various age groups. This study aims to evaluate the cervical cancer screening surveillance system in Bantul District in 2023, a region chosen for its low cervical cancer screening coverage and its significance as a representative area for rural public health challenges in Indonesia. Method: This descriptive study uses secondary data from the Visual Inspection with Acetic Acid (VIA) screening report conducted at Public Health Centers (PHCs) in Bantul District. The evaluation focuses on core functions (case detection, registration, reporting) and surveillance quality (completeness of data and reporting from PHCs). Results: Data were analyzed descriptively using percentages and frequencies. There were 27 PHCs, and 92,59% reported screening results. Jetis II PHC reported the highest screening coverage (9.60%) and Kasihan II PHC recorded the highest positive cases (21,15%). 24 PHCs (96%) used the patient registration form provided by the Health Office. Of 2.321 screened women, 52 were reported positive with 51.9% of cases having no follow-up records. The completeness of reporting from PHCs reached 95.68%, while the completeness of data averaged 61.76%, with a range of 4.35%-100%. Conclutions: The study relied on secondary data, which limited the ability to explore in-depth contextual factors and stakeholder perspectives, emphasizing the need for qualitative follow-up to enhance understanding. Capacity building of health workers in screening and reporting is required along with the development and implementation of Standard Operating Procedures (SOPs), which is critical to improving the program.